1977
DOI: 10.1002/qj.49710343809
|View full text |Cite
|
Sign up to set email alerts
|

The nocturnal jet

Abstract: Three case studies of the nocturnal jet at dawn are presented. Observations were made over southern England where the terrain is considerably less homogeneous than that over which previous published data concerning the jet have been obtained, for example the Great Plains and Wangara.It is shown that previously suggested layer models of the boundary layer can be usefully quantified togive the diurnal evolution of a layer-average wind. This model, which involves a decoupling of the flow in middle levels from sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(47 citation statements)
references
References 12 publications
1
46
0
Order By: Relevance
“…At night, winds at higher levels usually tend to accelerate by an inertial oscillation as a result of flow decoupling (Blackadar 1957). Near the surface, winds weaken owing to a combination of inertial effects and turbulent stress divergence around sunset (Thorpe and Guymer 1977;Baas et al 2012). At intermediate heights (some decameters above the surface), a ''crossing level'' exists where the wind remains relatively constant in magnitude.…”
Section: Model Descriptionmentioning
confidence: 99%
“…At night, winds at higher levels usually tend to accelerate by an inertial oscillation as a result of flow decoupling (Blackadar 1957). Near the surface, winds weaken owing to a combination of inertial effects and turbulent stress divergence around sunset (Thorpe and Guymer 1977;Baas et al 2012). At intermediate heights (some decameters above the surface), a ''crossing level'' exists where the wind remains relatively constant in magnitude.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The low-level jet of the Great Plains region of the United States has been extensively studied by among others, Hoecker (1963Hoecker ( ,1965; Blackadar (1957);Wexler (1961) and Bonner (1968). Other mid-to-higher latitude nocturnal low-level jets have been detected in southeastern Australia (Clarke et al, 1971), southern England (Thorpe and Guymer, 1977), northwestern Germany (Kraus er al., 1985), the United States Gulf coast (Hsu, 1979), and the coastal regions of northeastern United States and the Canadian Maritimes (Dickerson and Neumann, 1982). In the tropical and subtropical regions of the world, however, only a few documented cases of lowlevel nocturnal jets or wind maxima are in existence.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Thorpe and Guymer (1977) and Beyrich and Klose (1988) have analysed vector-time hodographs showing an inertial spiral and compared these with simple models with good results. Using a barotropic model, Logsdon and Revelle (1987) have shown that the inertial oscillation mechanism is most effective at latitudes 22-23" where the length of night matches the inertial period.…”
Section: Mechanismssustainingthewinternocturnallowleveljetmentioning
confidence: 99%